2015
DOI: 10.3892/br.2015.472
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diethylstilbestrol on the proliferation and tyrosinase activity of cultured human melanocytes

Abstract: Abstract. The aim of the present study was to observe the effects of different exogenous estrogen diethylstilbestrol (DES) concentrations on the human melanocyte proliferation and tyrosinase activity. Skin specimens were obtained following blepharoplasty, and the melanocytes were primary cultured and passaged to the third generation. The melanocytes were seeded in 96-well plates, each well had 5x10 3 cells. The medium was changed after 24 h, and contained 10 -4 -10 -8 M DES. After the melanocytes were incubate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In a previous study we found an increase in Melan-A + melanocytes in BN lesions (1). Androgen reduced tyrosinase activity in human melanocytes (34), while oestrogen promoted proliferation, tyrosinase activity and pigment synthesis (35). Oestrogen increased, but progesterone decreased pigment production in human melanocytes (10).…”
Section: Discussionmentioning
confidence: 77%
“…In a previous study we found an increase in Melan-A + melanocytes in BN lesions (1). Androgen reduced tyrosinase activity in human melanocytes (34), while oestrogen promoted proliferation, tyrosinase activity and pigment synthesis (35). Oestrogen increased, but progesterone decreased pigment production in human melanocytes (10).…”
Section: Discussionmentioning
confidence: 77%